Design and study the effect of inner bore diameter on the magnetic and optical properties of the unipolar lens - Mohammed.K.A. AL- Janan; R.Y. J. AL-Salih (مجلة بغداد للعلوم, 2023)
Many designs have been suggested for unipolar magnetic lenses based on changing the width of the inner bore and fixing the other geometrical parameters of the lens to improve the performance of unipolar magnetic lenses. The investigation of a study of each design included the calculation of its axial magnetic field the magnetization of the lens in addition to the magnetic flux density using the Finite Element Method (FEM) the Magnetic Electron Lenses Operation (MELOP) program version 1 at three different values of current density (6,4,2 A/mm2). As a result, the clearest values and behaviors were obtained at current density (2 A/mm2). it was found that the best magnetizing properties, the highest value of magnetic flux, the lowest value of band width of the axial magnetic field strength had been obtained when the width of the inner cavity was of (55 mm). The effect of current density on the optical properties has also been studied, the chromatic and spherical aberration values have been decreased significantly. Thus, lens was chosen as the best design among the proposed designs unipolar lens.